A study of Scrum @ S&P Global in the post-COVID-19 era: Unsuitable for remote work or just flawed implementation? - Przybyłek, Adam; Belter, Daniel; Conboy, Kieran (Information and software technology, 2025)
Although the COVID-19 pandemic is behind us, the seminal challenge for agile teams has not gone away, as “Work-From-Home (WFH) is here to stay”. Despite a wealth of literature documenting the challenges of applying agile methods in remote environments, practical guidance for overcoming these challenges remains limited. Furthermore, systematic meta-guidelines to help practitioners develop tailored, context-specific solutions are largely absent. This article reports on an Action Research project conducted at S&P Global 18 months after the company’s transition to a WFH model. The project aimed to evaluate existing adaptations to remote work, identify persistent issues, and develop strategies to address them. Our investigation revealed that while ad-hoc solutions — such as virtualizing Scrum ceremonies and shifting informal in-person conversations to Slack channels — enabled work continuity during the pandemic, they proved insufficient for tackling more complex challenges. Intriguingly, only two ongoing issues stemmed from misalignments between Scrum and remote settings, while the remainder were rooted in flawed Scrum implementation. With our guidance, the participating team not only rediscovered the “Inspect and Adapt” principle but also mastered a systematic approach to method tailoring, enabling them to devise measures that effectively resolved most of their issues. Our study reinforces prior findings indicating the applicability of Scrum beyond its traditional “home ground”, while also highlighting the need for remote teams to exhibit even greater discipline in adhering to the Scrum framework to navigate the additional challenges of remote work. We also observed a heightened necessity for more comprehensive documentation in remote settings to compensate for limited immediate access to colleague assistance, which consequently restricts knowledge sharing. Finally, the structured approach we employed offers valuable guidance for software companies seeking to identify and address operational inefficiencies in both remote and hybrid work environments. •Most issues stem from flawed Scrum implementation, not its mismatch with remote work.•Remote Scrum reveals hidden dysfunctions not apparent in traditional office settings.•Remote teams need more strategic documentation to enhance knowledge sharing.•Tailored Scrum with collaboration tools excels remotely, defying collocation assumptions.•Action Research guides practitioners to systematically refine their practices.